Thyroid Function Abnormalities in COVID-19 Patients - Wang, Weibin; Su, Xingyun; Ding, Yongfeng; Fan, Weina; Zhou, Weibin; Su, Junwei; Chen, Zhendong; Zhao, Hong; Xu, Kaijin; Ni, Qin; Xu, Xiaowei; Qiu, Yunqing; et al. (Frontiers in Endocrinology, 2021)
Purpose: The novel coronavirus COVID-19, has caused a worldwide pandemic, impairing several human organs and systems. Whether COVID-19 affects human thyroid function remains unknown. Methods: 84 hospitalized COVID-19 patients in the First Affiliated Hospital, Zhejiang University School of Medicine (Hangzhou, China) were retrospectively enrolled in this study, among which 22 cases had complete records of thyroid hormones. In addition, 91 other patients with pneumonia and 807 healthy subjects were included as controls. Results: We found that levels of total triiodothyronine (TT3) and thyroid stimulating hormone (TSH) were lower in COVID-19 patients than healthy group (p<0.001). Besides, TSH level in COVID-19 patients was obviously lower than non-COVID-19 patients (p<0.001). Within the group of COVID-19, 61.9% (52/84) patients presented with thyroid function abnormalities and the proportion of thyroid dysfunction was higher in severe cases than mild/moderate cases (74.6% vs. 23.8%, p < 0.001). Patients with thyroid dysfunction tended to have longer viral nucleic acid cleaning time (14.1 ± 9.4 vs. 10.6 ± 8.3 days, p = 0.088). To note, thyroid dysfunction was also associated with decreased lymphocytes (p < 0.001) and increased CRP (p = 0.002). The correlation between TT3 and TSH level seemed to be positive rather than negative in the early stage, and gradually turned to be negatively related over time. Conclusion: Thyroid function abnormalities are common in COVID-19 patients, especially in severe cases. This might be partially explained by nonthyroidal illness syndrome.